Seawater-based polymer coated self-suspending proppant as well as preparation method and application thereof

By covering specific polymers and surfactants on the surface of the proppant, the salt resistance and viscosity of seawater-based self-suspended proppants are enhanced, and the problem of poor suspension performance in offshore oil field fracturing is solved, and efficient offshore low-osmotic fracturing is achieved, reducing costs and environmental impacts.

CN120248211AActive Publication Date: 2025-07-04CHINA UNIV OF PETROLEUM (EAST CHINA)

Patent Information

Application Number
CN202510735254.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-04
Publication Date
2025-07-04
Estimated Expiration
2045-06-04

AI Technical Summary

Technical Problem

The existing self-suspended proppants in offshore oilfield fracturing have poor suspension performance due to poor salt resistance, which cannot meet the needs of low-osmosis fracturing at sea. The cost of freshwater configuration is high, and the use of seawater leads to a degradation of polymer cladding performance.

Method used

The seawater-based polymer-coated self-suspended proppant is used to coat the silane coupling agent KH570, acrylamide, hydrophobic monomer cetyldimethylallyl ammonium chloride, tetratail betaine monomer and sodium styrene sulfonate polymer layer on the surface of the proppant, and combine nonionic surfactant to enhance salt resistance and viscosity to form a composite network structure.

Benefits of technology

It improves the suspension capacity and transport performance of proppant in seawater, reduces fracturing costs, meets the fracturing needs of offshore low-permeability oil fields, and provides a green solution with economic and environmental benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120248211A_ABST
    Figure CN120248211A_ABST
Patent Text Reader

Abstract

The invention provides a seawater-based polymer coated self-suspending proppant as well as a preparation method and application thereof, and belongs to the technical field of oilfield fracturing exploitation. The proppant is prepared from the following raw materials: a proppant body, a silane coupling agent gamma-methacryloxypropyltrimethoxysilane, acrylamide, a hydrophobic monomer hexadecyl dimethyl allyl ammonium chloride, a twin-tailed betaine monomer, sodium p-styrenesulfonate, an initiator and a solvent. The self-suspending proppant and the nonionic surfactant are compounded for use so as to be applied to the fracturing fluid. On one hand, the polymer on the surface of the proppant has good salt tolerance and is dissolved after meeting seawater, so that the viscosity is increased; and on the other hand, the surfactant and the dissolved polymer coating layer generate a synergistic effect, so that a tackifying effect is achieved. The sand suspending effect is generated as the tackifying effect of normal fracturing fluid, and the seawater low-permeability fracturing requirement is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of oilfield fracturing exploitation, and particularly relates to a seawater-based polymer-coated self-suspending proppant, a preparation method thereof and an application thereof. Background Art

[0002] With the continuous expansion of the development degree of onshore oilfields, the recoverable reserves are getting smaller and smaller, and people gradually turn their research objects to offshore oilfields. As a main reservoir stimulation technology, hydraulic fracturing has been widely used in the development of low-permeability oil and gas. Its main action mechanism is to use a ground high-pressure pump unit to inject fracturing fluid into the reservoir at a displacement greater than the absorption capacity of the reservoir, forming a high-pressure artificial fracture in the wellbore. Then, a sand-carrying fluid containing proppant is injected into the fracture to support the fracture, forming several high-conductivity channels for oil and gas migration, so as to achieve the purpose of increasing production and injection.

[0003] Proppant is a key material for hydraulic fracturing construction. It can support the fracturing fracture, prevent the fracture from closing due to stress release, thus keeping the oil and gas channel unobstructed, improving the conductivity and increasing the recovery rate. Current research shows that in the fracturing operation of offshore oilfields, the selection and performance of proppants are directly related to the fracturing effect and economic benefits. Currently, the commonly used proppants in oilfields include artificial ceramsite and quartz sand. Although they have low costs, they are prone to sedimentation during offshore fracturing construction and are difficult to reach the far end of the fracture to provide effective support. In order to improve the suspension performance of proppants and enable them to migrate deep into the formation fractures, self-suspending proppants with low settling velocity and good support effect have been developed. Self-suspending proppants are coated with a layer of polymer on the surface of the proppant. The coating layer rapidly disperses and swells in water to form a polymer solution with a certain viscosity to effectively suspend the proppant. However, the self-suspending proppant system is mainly prepared with fresh water and faces the following problems in offshore fracturing engineering applications. First, the use of fresh water for preparation results in high development costs. Second, although seawater can save water resources and reduce costs, the seawater has a high salinity and is rich in metal ions such as Na + , K + , Ca 2+ , Mg 2+ etc. High concentrations will cause conformational changes in the polymer coating layer, cause the polymer chain segments to curl by compressing the double electric layer, reduce its performance, resulting in poor self-suspension ability and unable to meet the requirements of offshore fracturing.

[0004] Chinese Patent Document CN 109423271 A discloses a volume-expandable magnetic self-suspending proppant and its preparation method. The proppant is a magnetic proppant aggregate modified by a silane coupling agent, on which a water-based volume-expandable polymer material is grafted. The method includes: spraying a solution of the silane coupling agent onto the surface of the proppant aggregate to undergo a first reaction to obtain a coupling agent-modified magnetic proppant aggregate; spraying an emulsion of the water-based volume-expandable polymer material onto the silane coupling agent-modified magnetic proppant aggregate to undergo a second reaction to obtain the volume-expandable magnetic self-suspending proppant. The magnetic self-suspending proppant of the present invention has good self-suspending function and also has good magnetic induction. However, the proppant obtained by this invention has room for improvement in salt tolerance and cannot meet the requirements of offshore fracturing.

[0005] Therefore, for offshore low-permeability oilfields, it is urgent to develop new proppants that not only need to have excellent suspension characteristics but also meet higher salt tolerance, so as to overcome the defects of the existing technology, which is of great significance for the efficient development of offshore low-permeability oilfields. Summary of the Invention

[0006] Aiming at the deficiencies of the existing technology, the present invention provides a seawater-based polymer-coated self-suspending proppant, its preparation method and application. The present invention first coats a layer of polymer on the surface of the proppant. The polymer coating layer is polymerized from a silane coupling agent KH570, acrylamide (AM), a hydrophobic monomer cetyl dimethyl allyl ammonium chloride (C 16 DMAAC), a twin-tailed betaine monomer (DSDAP), and sodium styrene sulfonate (SSS). The self-suspending proppant of the present invention is used in combination with a non-ionic surfactant in a fracturing fluid. On the one hand, the polymer on the surface of the proppant of the present invention has good salt tolerance and dissolves in seawater, increasing its viscosity; on the other hand, the surfactant and the dissolved polymer coating layer produce a synergistic effect, achieving a viscosity-increasing effect. It produces a sand-suspending effect similar to the viscosity-increasing effect of a normal fracturing fluid, meeting the requirements of seawater low-osmotic pressure fracturing.

[0007] The technical solution of the present invention is as follows: The present invention provides a seawater-based polymer-coated self-suspending proppant, which is prepared from the following raw materials: proppant, silane coupling agent γ-methacryloxypropyltrimethoxysilane (KH570), acrylamide (AM), hydrophobic monomer cetyl dimethyl allyl ammonium chloride (C 16 DMAAC), twin-tailed betaine monomer (DSDAP), sodium styrene sulfonate (SSS), initiator, and solvent.

[0008] Preferably according to the present invention, the preparation method of the twin-tailed betaine monomer (DSDAP) includes the steps: (1) Dissolve (2-bromomethyl)dimethylamine, sodium methanesulfonate, and potassium carbonate in N,N-dimethylformamide (DMF), conduct a reflux reaction by heating, and then obtain 3-(dimethylamino)propane-1-sulfonate (SDAP) through post-treatment; (2) Dissolve 3-(dimethylamino)propane-1-sulfonate (SDAP) in absolute ethanol, and dropwise add an absolute ethanol solution of 1,4-dichloro-2-butene (DB). Conduct a reflux reaction by heating, and then obtain the gemini betaine monomer (DSDAP) through post-treatment.

[0009] Preferably, in step (1), the mass ratio of (2-bromomethyl)dimethylamine, sodium methanesulfonate, and potassium carbonate is 1:1.0 - 1.6:2, preferably 1:1.03:2.

[0010] Preferably, in step (1), the mass ratio of (2-bromomethyl)dimethylamine to the volume of DMF is 1:1 - 10 g / mL, preferably 1:2.2 g / mL.

[0011] Preferably, in step (1), the reflux reaction temperature is 60 - 80 °C, and the reaction time is 6 - 12 h, preferably the reaction temperature is 80 °C and the reaction time is 8 h. The reflux reaction is carried out under stirring conditions.

[0012] Preferably, in step (1), the post-treatment method includes the steps: cool the reaction solution to room temperature, remove DMF by vacuum distillation, dissolve the viscous residue after vacuum distillation with ethanol, heat to 50 °C and stir for 5 - 10 min, add deionized water, shake and then let it stand for liquid separation, discard the aqueous phase; dry the organic phase with anhydrous sodium sulfate, filter and then rotary evaporate; then add it to a silica gel column, and the eluent is a mixed solution of ethyl acetate and methanol, where the volume ratio of ethyl acetate to methanol is 9:1, collect the target fraction, and rotary evaporate to remove the solvent to obtain a white solid, which is 3-(dimethylamino)propane-1-sulfonate.

[0013] Preferably, in step (2), the mass ratio of 3-(dimethylamino)propane-1-sulfonate (SDAP) to 1,4-dichloro-2-butene (DB) is 1.7 - 3.1:1.0, preferably 2.6:1.0.

[0014] Preferably, in step (2), the mass ratio of 3-(dimethylamino)propane-1-sulfonate (SDAP) to the volume of absolute ethanol is 0.5 - 2 g / mL.

[0015] Preferably, in step (2), the mass concentration of the absolute ethanol solution of 1,4-dichloro-2-butene (DB) is 0.1-1 g / mL; the dropping rate of the absolute ethanol solution of 1,4-dichloro-2-butene (DB) is 1-5 drops per second; the dropping of the absolute ethanol solution of 1,4-dichloro-2-butene (DB) is carried out under stirring at 40-70 °C.

[0016] Preferably, in step (2), the heating reflux reaction temperature is 40-70 °C, the reaction time is 12-20 h, preferably the reaction temperature is 65 °C and the reaction time is 18 h. The heating reflux reaction is carried out under stirring conditions.

[0017] Preferably, in step (2), the post-treatment method includes the steps of: the reaction solution is subjected to vacuum distillation, the obtained product is dissolved in acetone, cooled and crystallized, washed with acetone, filtered, and dried to obtain the gemini betaine monomer (DSDAP).

[0018] According to the preference of the present invention, the gemini betaine monomer (DSDAP) has the structure shown in the following formula I:

[0019] According to the preference of the present invention, the proppant is selected from quartz sand or ceramsite.

[0020] According to the preference of the present invention, the initiator includes a chain extender, an oxidant, a reductant, and an initiation catalyst.

[0021] Preferably, the chain extender is an aqueous solution of polyamine, the polyamine is tetramethylethylenediamine or dimethylethylenediamine, preferably tetramethylethylenediamine. The mass concentration of the chain extender is 0.02-0.16%, preferably 0.08%.

[0022] Preferably, the oxidant is an aqueous solution of potassium persulfate, and the reductant is an aqueous solution of sodium bisulfite. The mass concentrations of the aqueous solution of potassium persulfate and the aqueous solution of sodium bisulfite are both 0.005-0.009%, preferably 0.007%.

[0023] Preferably, the initiation catalyst is an aqueous solution of ferric chloride, and the mass concentration of the aqueous solution of ferric chloride is 0.0005-0.00225%, preferably 0.00125%.

[0024] According to the preference of the present invention, the solvent is distilled water.

[0025] According to the preference of the present invention, the mass ratio of acrylamide (AM), the hydrophobic monomer cetyl dimethyl allyl ammonium chloride (C 16 DMAAC), the gemini betaine monomer (DSDAP), and sodium styrene sulfonate (SSS) is 5-6:0.3-0.5:4-5:1, preferably 5.8:0.33:4.19:1.

[0026] Preferably according to the present invention, the mass ratio of the proppant, the silane coupling agent γ-methacryloxypropyltrimethoxysilane (KH570), and acrylamide (AM) is 100 - 500:1:0.5 - 4, preferably 100:1:0.64.

[0027] Preferably according to the present invention, the total mass percentage of acrylamide (AM), the hydrophobic monomer cetyl dimethyl allyl ammonium chloride (C 16 DMAAC), the twin-tailed betaine monomer (DSDAP), and sodium styrene sulfonate (SSS) in the solvent is 15% - 30%, preferably 25%.

[0028] Preferably according to the present invention, the mass ratio of the initiator to acrylamide (AM) is 1:0.1 - 0.5, preferably 1:0.128.

[0029] Preferably according to the present invention, the particle size of the seawater-based polymer-coated self-suspending proppant is 550 μm - 600 μm; the structural schematic is as follows:

[0030] The preparation method of the above-mentioned seawater-based polymer-coated self-suspending proppant includes the steps: (1) The proppant is washed successively with distilled water and an organic solvent to remove organic and inorganic impurities on the surface of the proppant, and then dried; the silane coupling agent γ-methacryloxypropyltrimethoxysilane (KH570) is added, soaked, and dried to obtain the pretreated proppant; (2) Acrylamide (AM), the hydrophobic monomer cetyl dimethyl allyl ammonium chloride (C 16 DMAAC), the twin-tailed betaine monomer (DSDAP), and sodium styrene sulfonate (SSS) are dissolved in the solvent, and the pH value of the system is adjusted; the pretreated proppant is added, fully dispersed, the initiator is dropped, and after copolymerization reaction, it is dried, pulverized, and sieved to obtain the seawater-based polymer-coated self-suspending proppant.

[0031] Preferably according to the present invention, in step (1), the organic solvent is selected from at least one of ethanol, acetone, or petroleum ether.

[0032] Preferably according to the present invention, in step (1), the soaking time is 3 - 8 h, preferably 6 h; the soaking temperature is 50 - 60 °C, preferably 50 °C; the soaking is carried out under stirring conditions.

[0033] Preferably according to the present invention, in step (2), the pH value of the system is adjusted to 7 using an aqueous sodium hydroxide solution with a mass concentration of 15% - 30%.

[0034] Preferably according to the present invention, in step (2), the dropping rate of the initiator is 1-2 drops per second; the dropping is carried out under stirring, protection of a protective gas, and at a temperature of 35-40°C. The protective gas is nitrogen or argon.

[0035] Preferably according to the present invention, in step (2), the copolymerization reaction temperature is 35-40°C, the reaction time is 4-6 h, preferably the reaction temperature is 35°C and the reaction time is 6 h. The copolymerization reaction is carried out under stirring and protection of a protective gas. The protective gas is nitrogen or argon.

[0036] The application of the above seawater-based polymer-coated self-suspending proppant is applied to hydraulic fracturing in offshore low-permeability oilfields or high-salinity low-permeability oilfields.

[0037] Preferably according to the present invention, the application method includes the steps of: fully dispersing the seawater-based polymer-coated self-suspending proppant and a non-ionic surfactant in seawater or high-mineralization water to obtain a sand-carrying fluid for use in hydraulic fracturing in offshore low-permeability oilfields or high-salinity low-permeability oilfields.

[0038] Preferably, the non-ionic surfactant is fatty alcohol polyoxyethylene ether AEO-3 or Span-80, preferably fatty alcohol polyoxyethylene ether AEO-3.

[0039] Preferably, the mass ratio of the seawater-based polymer-coated self-suspending proppant to the non-ionic surfactant is 40-60:1, preferably 50:1.

[0040] Preferably, in the sand-carrying fluid, the mass ratio of the seawater-based polymer-coated self-suspending proppant to the volume of seawater or high-mineralization water is 0.01-1 g / mL, preferably 0.15 g / mL.

[0041] Preferably, the salinity of the seawater is 35000 mg / L; the salinity of the high-mineralization water is greater than 35000 mg / L and less than or equal to 200000 mg / L.

[0042] The technical features and beneficial effects of the present invention are as follows: (1) The self-suspending proppant of the present invention is used for hydraulic fracturing, which can achieve the need not to add a thickener required for preparing a sand-carrying fluid in a conventional fracturing process. The polymer coating layer on the surface of the proppant dissolves in water or seawater, and the sand-carrying fluid after the polymer dissolves in water or seawater has viscoelasticity, the fluid density increases, and the viscosity increases, thereby promoting the deep migration of the proppant, reducing the use of fracturing fluid chemicals such as slickwater, simplifying the fracturing process, and reducing the fracturing cost.

[0043] (2) The polymer-coated self-suspending proppant provided by the present invention has good salt tolerance. This is attributed to the introduction of a molecular structure that confers salt tolerance into the proppant. On the one hand, the introduction of the hydrophobic monomer cetyl dimethyl allyl ammonium chloride increases the hydrophobic groups on the polymer chain, enhances the hydrophobic association, constructs supramolecular aggregates, and these hydrophobic long chains entangle with each other to form a spatial network structure. This network structure has a stronger ability to envelope or adsorb water molecules, increases the hydrodynamic volume of the polymer, and shows an increase in viscosity. On the other hand, the twin-tailed betaine monomer DSDAP contains a certain number of cationic and anionic groups. Its special molecular structure gives it a certain anti-polyelectrolyte effect. As the salinity of the aqueous solution continuously increases, the mutual attraction between positive and negative ions will be shielded by salt ions, thereby enhancing the interaction between solvents, making the molecular structure more extended, enabling the polymer to have a higher viscosity in seawater, showing the salt thickening property. Moreover, the sulfonic acid group has a strong hydration effect, which can resist the destructive effect of salt ions and at the same time increase the rigidity of the polymer chain.

[0044] (3) The polymer coating layer in the proppant of the present invention has active groups such as sulfonic acid groups and quaternary ammonium cationic groups after the micelles formed in seawater or water are broken, and contains a non-ionic surfactant. Through the action of multiple active groups, the breaking solution can reduce the interfacial tension and improve the oil displacement efficiency of the reservoir.

[0045] (4) The polymer-coated self-suspending proppant of the present invention breaks through the traditional dependence on fresh water, utilizes the excellent ionic environment of seawater to significantly improve the suspension and transportation capacity of the proppant, reduces the consumption of fresh water for fracturing, and provides a green solution with both economic and environmental benefits for the development of offshore low-permeability oil and gas resources.

[0046] (5) A new initiation system is introduced in the synthesis of the polymer-coated self-suspending proppant of the present invention. On the basis of the ordinary redox initiation system, an efficient chain extender and an initiation catalyst are introduced to form an efficient initiation system, which greatly promotes the rate of the redox reaction, increases the activity of free radicals, and realizes high-efficiency initiation with a low addition amount. Compared with the ordinary redox initiation system, the polymer-coated self-suspending proppant synthesized by this system makes the viscosity of the sand-carrying fluid higher and the suspension ability stronger.

[0047] (6) When the polymer-coated self-suspending proppant of the present invention is used, it is compounded with a non-ionic surfactant, and there is a synergistic effect between the two. When the dosage of the non-ionic surfactant is small, the hydrophilic chain of the surfactant wraps the hydrophobic chain of the polymer, playing a role in disintegrating the intermolecular hydrophobic association, and the viscosity of the system decreases. Continuing to increase the surfactant concentration, the hydrophobic chains of the surfactant and the polymer form mixed micelles. The mixed micelles wrap the hydrophobic segments on different molecular chains in the same micelle, playing a bridging role. The polymer coating layer forms a large composite network structure through the bridging points, and the viscosity increases. When the surfactant concentration is too high, the micelles entangle with each other, the network structure continuously expands, the viscosity increases accordingly, and the self-suspending proppant is not easy to settle, so that it can migrate to the far end of the fracture to provide effective support. Description of the Drawings

[0048] Figure 1 It is the synthesis route diagram of the gemini betaine monomer (DSDAP) of the present invention; Figure 2 It is the synthesis route diagram of the polymer-coated self-suspending proppant of the present invention; Figure 3 It is the infrared spectrum diagram of the pretreated proppant prepared in Example 1 of the present invention; Figure 4 It is the infrared spectrum diagram of the polymer-coated self-suspending proppant prepared in Example 1 of the present invention. Detailed Embodiments

[0049] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and not to limit the scope of the present invention. The experimental methods without specific conditions noted in the following embodiments are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer. Example 1

[0050] A preparation method of a seawater-based polymer-coated self-suspending proppant: 1. Synthesis of the gemini betaine monomer DSDAP, the route is as Figure 1 shown (1) Dissolve 13.8 g of (2-bromomethyl)dimethylamine in 30 mL of DMF. Then add 14.2 g of sodium methanesulfonate and 27.6 g of potassium carbonate, and stir until dissolved. Heat to 80 °C and reflux with stirring for 8 h. After the reaction is completed, cool to room temperature, remove DMF by vacuum distillation. Dissolve the viscous residue after vacuum distillation in 20 mL of ethanol, heat to 50 °C and stir for 5 min, add 40 mL of deionized water, transfer to a separatory funnel, shake and let stand for liquid separation, and discard the aqueous phase. Dry the organic phase with anhydrous sodium sulfate, filter and then rotary evaporate. Then add the sample to a silica gel column (eluent: ethyl acetate / methanol volume ratio = 9:1), collect the target fraction. Rotary evaporate to remove the solvent to obtain a white solid, which is 3-(dimethylamino)propane-1-sulfonate.

[0051] (2) Weigh 16.5 g of 3-(dimethylamino)propane-1-sulfonate (SDAP) and dissolve it in 30 mL of absolute ethanol. Then add it to a three-necked flask equipped with a thermometer, a stirrer and a reflux condenser. Heat to 65 °C. Dissolve 6.25 g of 1,4-dichloro-2-butene (DB) in 30 mL of absolute ethanol and place it in a constant pressure dropping funnel. Add it dropwise to the three-necked flask under stirring conditions. The dropping rate of the absolute ethanol solution of 1,4-dichloro-2-butene (DB) is 2 drops per second. Heat and reflux with stirring at 65 °C for 18 h. After the reaction is completed, distill off the unreacted monomers and absolute ethanol under reduced pressure. Dissolve the product after vacuum distillation in 120 mL of acetone, then cool and crystallize in a refrigerator, rinse the synthesized product with acetone three times, then filter by suction, and finally dry the product in a vacuum drying oven to constant weight to obtain the gemini betaine monomer DSDAP.

[0052] 2. Synthesis of polymer-coated self-suspended proppant, the route is as Figure 2 shown (1) Rinse the quartz sand (20-40 mesh) proppant with distilled water, ethanol, and acetone several times in sequence to remove impurities on the surface of the quartz sand, and dry it. Weigh 4 kg of quartz sand, add 40 g of silane coupling agent (KH570), soak and stir at 50 °C for 6 h, filter, and dry in vacuum to obtain the pretreated proppant.

[0053] The infrared spectrum of the pretreated proppant is as Figure 3 . In the spectral curve of the pretreated proppant, the characteristic peaks of methyl and methylene are around 2840~2980 cm -1 , the C=O vibration peak in the coupling agent is at 1781 cm -1 , the Si-OH bending vibration absorption peak is at 960 cm -1 , and the symmetric contraction vibration peak of the Si-O-Si bond is around 800 cm -1 ; at 2300 cm -1The C=C characteristic peak appeared at , indicating that the silane coupling agent was chemically bonded to the hydroxyl groups on the surface of the quartz sand, and the coupling agent was successfully grafted onto the proppant surface.

[0054] (2) Weigh 25.60 g acrylamide (AM), 1.48 g hydrophobic monomer hexadecyl dimethyl allyl ammonium chloride (C 16 DMAAC), 18.50g of twin-tailed betaine monomer (DSDAP), and 4.42g of heat-resistant and salt-resistant monomer sodium styrene sulfonate (SSS) were added into 200g of distilled water and stirred at a speed of 600r / min until completely dissolved. The pH value of the system was adjusted to 7 with a 15% mass concentration NaOH aqueous solution. Then the obtained solution was added into a three-necked flask, and N2 was passed into the three-necked flask for 30 minutes to remove oxygen in the system to obtain a surface coating liquid.

[0055] (3) Add the pretreated proppant to the surface coating liquid, fully disperse it, raise the temperature to 35°C, keep stirring the reaction under N2 protection, and add 0.08% tetramethylethylenediamine aqueous solution (the mass of tetramethylethylenediamine is 0.04g), 0.007% potassium persulfate aqueous solution (the mass of potassium persulfate is 0.0035g), 0.007% sodium bisulfite aqueous solution (the mass of sodium bisulfite is 0.0035g), and 0.00125% ferric chloride aqueous solution (the mass of ferric chloride is 0.000625g) drop by drop into the three-necked flask in sequence using a constant temperature and pressure funnel every 10 minutes under stirring, at a dropping rate of 1 drop per second. After the copolymerization and stirring reaction at 35° C. for 6 hours, the polymer was taken out, cut into pieces, dried in a drying oven at 80° C. to constant weight, and then crushed with a pulverizer and sieved to obtain a polymer-coated self-suspending proppant with a particle size of 580 μm.

[0056] Polymer coated self-suspending proppants such as Figure 4 As shown. 3444 cm -1 and 1665 cm -1 There are two absorption peaks at 1588cm, which correspond to the stretching vibration absorption peaks of NH and C=O in acrylamide respectively; -1 and 1450 cm -1 The characteristic absorption peaks at 810 cm-1 correspond to the two C=C stretching vibration absorption peaks in the aromatic ring skeleton structure. -1 The absorption peak of the aromatic ring at 1330 cm -1 The stretching vibration peak of -N-CH3 is at 982 cm -1 The characteristic absorption peak of the quaternary ammonium salt group is 731 cm-1 The peak at this position is the rocking vibration peak of the long-chain alkyl, indicating the hydrophobic monomer C 16 DMAAC was also successfully introduced into the polymer molecular chain; 2928.84 cm -1 The peaks at 1650.00 cm -1 are related to -CH2- and -CH3 on the twin-tailed betaine monomer DSDAP. Combining with the peak at 1190 cm -1 which is the stretching vibration peak of S=O on the sulfonic acid group, and the peak at 1040 cm -1 which is the stretching vibration peak of S-O on the sulfonic acid group. The above results indicate that the polymer has the characteristic absorption peaks of the twin-tailed betaine monomer DSDAP functional groups.

[0057] The application of the above seawater-based polymer-coated self-suspending proppant is applied to hydraulic fracturing in offshore low-permeability oilfields. The application method includes the steps: Add 100 mL of simulated seawater (salinity of 35000 mg / L) or high-salinity water (salinity of 200000 mg / L) for preparing the liquid into a container, turn on the stirrer, add 15 g of the polymer-coated self-suspending proppant and 0.3 g of the non-ionic surfactant fatty alcohol polyoxyethylene ether AEO-3. After fully mixing evenly, a sand-carrying fluid with a sand ratio of 15% is obtained. Example 2

[0058] A preparation method of a seawater-based polymer-coated self-suspending proppant is as described in Example 1, except that in the synthesis of the polymer-coated self-suspending proppant, the addition amount of the twin-tailed betaine monomer (DSDAP) is 19.5 g. Other steps and conditions are the same as in Example 1.

[0059] The application method of the above seawater-based polymer-coated self-suspending proppant is the same as in Example 1. Example 3

[0060] A preparation method of a seawater-based polymer-coated self-suspending proppant is as described in Example 1, except that in the synthesis of the polymer-coated self-suspending proppant, the addition amount of the hydrophobic monomer cetyl dimethyl allyl ammonium chloride (C 16 DMAAC) is 1.8 g. Other steps and conditions are the same as in Example 1.

[0061] The application method of the above seawater-based polymer-coated self-suspending proppant is the same as in Example 1. Example 4

[0062] A preparation method of a seawater-based polymer-coated self-suspending proppant is as described in Example 1, except that the mass of the quartz sand is 6 kg. Other steps and conditions are the same as in Example 1.

[0063] The application method of the above seawater-based polymer-coated self-suspending proppant is the same as that in Example 1. Example 5

[0064] A preparation method of a seawater-based polymer-coated self-suspending proppant is the same as that described in Example 1, except that the addition amount of silane coupling agent KH570 is 8 g. Other steps and conditions are the same as those in Example 1.

[0065] The application method of the above seawater-based polymer-coated self-suspending proppant is the same as that in Example 1. Example 6

[0066] A preparation method of a seawater-based polymer-coated self-suspending proppant is the same as that in Example 1.

[0067] The application of the above seawater-based polymer-coated self-suspending proppant is the same as that described in Example 1, except that the non-ionic surfactant is Span-80. Other steps and conditions are the same as those in Example 1.

[0068] The application method of the above seawater-based polymer-coated self-suspending proppant is the same as that in Example 1. Example 7

[0069] A preparation method of a seawater-based polymer-coated self-suspending proppant is the same as that in Example 1.

[0070] The application of the above seawater-based polymer-coated self-suspending proppant is the same as that described in Example 1, except that the addition amount of non-ionic surfactant fatty alcohol polyoxyethylene ether AEO-3 is 0.25 g. Other steps and conditions are the same as those in Example 1.

[0071] The application method of the above seawater-based polymer-coated self-suspending proppant is the same as that in Example 1. Example 8

[0072] A preparation method of a seawater-based polymer-coated self-suspending proppant is the same as that described in Example 1, except that the mass concentration of ferric chloride aqueous solution is 0.002% (where the mass of ferric chloride is 0.001 g). Other steps and conditions are the same as those in Example 1.

[0073] The application method of the above seawater-based polymer-coated self-suspending proppant is the same as that in Example 1. Comparative Example 1

[0074] A preparation method of a proppant is the same as that described in Example 1, except that the twin-tailed betaine monomer (DSDAP) is replaced with N,N-dimethyl(methacryloyloxyethyl)aminopropylsulfonate inner salt (DMAPS). Other steps and conditions are the same as those in Example 1.

[0075] The application method of the above proppant is the same as that in Example 1. Comparative Example 2

[0076] A preparation method of a proppant is the same as that described in Example 1, except that the hydrophobic monomer cetyl dimethyl allyl ammonium chloride (C 16 DMAAC) is not added. Other steps and conditions are the same as those in Example 1.

[0077] The application method of the above proppant is the same as that in Example 1. Comparative Example 3

[0078] A preparation method of a proppant is the same as that described in Example 1, except that the gemini betaine monomer (DSDAP) is not added. Other steps and conditions are the same as those in Example 1.

[0079] The application method of the above proppant is the same as that in Example 1. Comparative Example 4

[0080] A preparation method of a proppant is the same as that in Example 1.

[0081] The application of the above proppant is the same as that described in Example 1, except that the non-ionic surfactant fatty alcohol polyoxyethylene ether AEO-3 is not added. Other steps and conditions are the same as those in Example 1.

[0082] The application method of the above proppant is the same as that in Example 1. Comparative Example 5

[0083] A preparation method of a proppant is the same as that described in Example 1, except that only potassium persulfate and sodium bisulfite are added to the initiation system, and tetramethylethylenediamine and ferric chloride are not added. Other steps and conditions are the same as those in Example 1.

[0084] The application method of the above proppant is the same as that in Example 1. Comparative Example 6

[0085] A proppant, the proppant is single quartz sand (20-40 mesh).

[0086] The application method of the above proppant is the same as that in Example 1.

[0087] Test Example 1 Suspension performance test. This experiment is used to test the suspension ability of the proppants prepared in the examples and comparative examples. The test method is as follows: Respectively take the sand-carrying fluids (the salinity of the simulated seawater used is 35000 mg / L) of Examples 1-8 and Comparative Examples 1-6 that are mixed evenly and pour them into a 10 mL graduated cylinder. Let them stand still at a temperature of 25 °C or 90 °C, observe the dispersion state of the proppant in seawater, and record the time required for the proppant to completely settle, which is the suspension time. The test results are shown in Table 1.

[0088] Take Examples 1 - 8 and Comparative Examples 1 - 6, pour the uniformly mixed proppant-carrying fluid (the salinity of the high salinity water used is 200000 mg / L) into a 10 mL graduated cylinder, let it stand at a temperature of 25 °C, observe the dispersion state of the proppant in seawater, and record the time required for the proppant to completely settle, which is the suspension time. The test results are shown in Table 2.

[0089] Table 1 Record Table of Suspension Time of Proppant-Carrying Fluid Prepared with Simulated Seawater

[0090] Table 2 Record Table of Suspension Time of Proppant-Carrying Fluid Prepared with High Salinity Water with a Salinity of 200000 mg / L

[0091] Test Example 2 Viscosity-increasing ability test. This experiment is used to test the viscosity-increasing ability of the proppants prepared in the examples and comparative examples. The test method is as follows: Take Examples 1 - 8 and Comparative Examples 1 - 6, the uniformly mixed proppant-carrying fluid (the salinity of the simulated seawater used is 35000 mg / L), filter the proppant-carrying fluid to remove the proppant, and take the filtrate respectively to test the viscosity with a six-speed rotational viscometer at 25 °C and 90 °C. The experimental results are shown in Table 3.

[0092] Table 3 Viscosity Data of Different Proppants

[0093] Test Example 3 Interfacial tension test of the gel-breaking fluid. This experiment is used to test the interfacial tension of the gel-breaking fluid of the proppants prepared in the examples and comparative examples. The test method is as follows: (1) Take 50 mL of the uniformly mixed proppant-carrying fluid (the salinity of the simulated seawater used is 35000 mg / L) from Examples 1 - 8 and Comparative Examples 1 - 6, add 0.005 g of the gel-breaking agent potassium persulfate, set the gel-breaking temperature to 90 °C, and the gel-breaking time to 2 h. After the gel-breaking is completed, take out the gel-breaking fluid for standby; (2) Use a TX-500C interfacial tension meter to test the interfacial tension of the gel-breaking fluid at 60 °C. The experimental results are shown in Table 4.

[0094] Table 4 Interfacial Tensions of Different Gel-Breaking Fluids

[0095] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or perform equivalent replacements for some of the technical features. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.

Claims

1. A seawater-based polymer-coated self-suspending proppant, characterized in that, It is prepared from the following raw materials: proppant, silane coupling agent γ-methacryloxypropyltrimethoxysilane, acrylamide, hydrophobic monomer cetyl dimethyl allyl ammonium chloride, twin-tailed betaine monomer, sodium styrene sulfonate, initiator, solvent; The preparation method of the twin-tailed betaine monomer includes the steps: (1) Dissolve (2-bromomethyl) dimethylamine, sodium methanesulfonate and potassium carbonate in N,N-dimethylformamide, carry out a heating reflux reaction, and then obtain 3-(dimethylamino) propane-1-sulfonate through post-treatment; (2) Dissolve 3-(dimethylamino) propane-1-sulfonate in absolute ethanol, dropwise add an absolute ethanol solution of 1,4-dichloro-2-butene, carry out a heating reflux reaction, and then obtain the twin-tailed betaine monomer through post-treatment; The initiator includes a chain extender, an oxidant, a reductant and an initiation catalyst; the chain extender is an aqueous solution of polyamine, and the polyamine is tetramethylethylenediamine or dimethylethylenediamine; the oxidant is an aqueous solution of potassium persulfate, and the reductant is an aqueous solution of sodium bisulfite; the initiation catalyst is an aqueous solution of ferric chloride; The mass ratio of acrylamide, hydrophobic monomer cetyl dimethyl allyl ammonium chloride, twin-tailed betaine monomer, and sodium styrene sulfonate is 5-6:0.3-0.5:4-5:1; the mass ratio of proppant, silane coupling agent γ-methacryloxypropyltrimethoxysilane, and acrylamide is 100-500:1:0.5-4; the mass ratio of the initiator to acrylamide is 1:0.1-0.

5.

2. The seawater-based polymer-coated self-suspending proppant according to claim 1, wherein The preparation method of the twin-tailed betaine monomer includes one or more of the following conditions: i. In step (1), the mass ratio of (2-bromomethyl) dimethylamine, sodium methanesulfonate, and potassium carbonate is 1:1.0-1.6:2; ii. In step (1), the mass ratio of (2-bromomethyl) dimethylamine to the volume of N,N-dimethylformamide is 1:1-10 g / mL; iii. In step (1), the heating reflux reaction temperature is 60-80 °C, the reaction time is 6-12 h, and the heating reflux reaction is carried out under stirring conditions; iv. In step (2), the mass ratio of 3-(dimethylamino) propane-1-sulfonate to 1,4-dichloro-2-butene is 1.7-3.1:1.0; v. In step (2), the mass ratio of 3-(dimethylamino) propane-1-sulfonate to the volume of absolute ethanol is 0.5-2 g / mL; vi. In step (2), the mass concentration of the absolute ethanol solution of 1,4-dichloro-2-butene is 0.1-1 g / mL; the dropping rate of the absolute ethanol solution of 1,4-dichloro-2-butene is 1-5 drops per second; the dropping of the absolute ethanol solution of 1,4-dichloro-2-butene is carried out under stirring and at 40-70 °C; vii. In step (2), the heating reflux reaction temperature is 40-70 °C, the reaction time is 12-20 h, and the heating reflux reaction is carried out under stirring conditions.

3. The seawater-based polymer-coated self-suspending proppant according to claim 1, wherein It includes one or more of the following conditions: i. The proppant is selected from quartz sand or ceramsite; ii. The solvent is distilled water.

4. The seawater-based polymer-coated self-suspending proppant according to claim 1, wherein The mass concentration of the chain extender is 0.02 - 0.16%; the mass concentrations of the aqueous potassium persulfate solution and the aqueous sodium bisulfite solution are both 0.005 - 0.009%; the mass concentration of the aqueous ferric chloride solution is 0.0005 - 0.00225%.

5. The seawater-based polymer-coated self-suspending proppant according to claim 1, wherein The total mass percentage of acrylamide, the hydrophobic monomer cetyl dimethyl allyl ammonium chloride, the gemini betaine monomer, and sodium styrene sulfonate in the solvent is 15% - 30%.

6. The preparation method of the seawater-based polymer-coated self-suspending proppant according to any one of claims 1-5, characterized in that, It includes the steps: (1) The proppant is washed successively with distilled water and an organic solvent to remove organic and inorganic impurities on the surface of the proppant, and then dried; γ-methacryloxypropyltrimethoxysilane, a silane coupling agent, is added, soaked, and dried to obtain the pretreated proppant; (2) Acrylamide, the hydrophobic monomer cetyl dimethyl allyl ammonium chloride, the gemini betaine monomer, and sodium styrene sulfonate are dissolved in a solvent, and the pH value of the system is adjusted; the pretreated proppant is added, fully dispersed, an initiator is added dropwise, and after copolymerization reaction, it is dried, crushed, and sieved to obtain the seawater-based polymer-coated self-suspending proppant.

7. The preparation method of the seawater-based polymer-coated self-suspending proppant according to claim 6, wherein, It includes one or more of the following conditions: i. In step (1), the organic solvent is selected from at least one of ethanol, acetone, or petroleum ether; ii. In step (1), the soaking time is 3 - 8 h; the soaking temperature is 50 - 60 °C; the soaking is carried out under stirring conditions; iii. In step (2), the pH value of the system is adjusted to 7 using an aqueous sodium hydroxide solution with a mass concentration of 15% - 30%; iv. In step (2), the dropping rate of the initiator is 1 - 2 drops per second; the dropping is carried out under stirring, under the protection of an inert gas, at 35 - 40 °C; the inert gas is nitrogen or argon; v. In step (2), the copolymerization reaction temperature is 35 - 40 °C, and the reaction time is 4 - 6 h; the copolymerization reaction is carried out under stirring and under the protection of an inert gas; the inert gas is nitrogen or argon.

8. The application of the seawater-based polymer-coated self-suspending proppant according to any one of claims 1-5, characterized in that, It is applied to hydraulic fracturing in offshore low-permeability oilfields or high-salinity low-permeability oilfields.

9. The application of the seawater-based polymer-coated self-suspending proppant according to claim 8, characterized in that, The application method includes the steps: The seawater-based polymer-coated self-suspending proppant and a non-ionic surfactant are fully dispersed in seawater or high-mineralization water to obtain a sand-carrying fluid, which is applied to hydraulic fracturing in offshore low-permeability oilfields or high-salinity low-permeability oilfields.

10. The application of the seawater-based polymer-coated self-suspending proppant according to claim 9, characterized in that, It includes one or more of the following conditions: i. The non-ionic surfactant is fatty alcohol polyoxyethylene ether AEO-3 or Span-80; ii. The mass ratio of the seawater-based polymer-coated self-suspending proppant to the non-ionic surfactant is 40 - 60:1; iii. In the sand-carrying fluid, the mass ratio of the seawater-based polymer-coated self-suspending proppant to the volume of seawater or high-mineralization water is 0.01 - 1 g / mL; iv. The salinity of seawater is 35000 mg / L; the salinity of high-mineralization water is greater than 35000 mg / L and less than or equal to 200000 mg / L.

Citation Information

Patent Citations

  • Volume-expansion magnetic self-suspension propping agent and preparation method thereof

    CN109423271A

  • Preparation method for self-suspension propping agent in laboratory

    CN106634939A

  • Betaine type double-tailed hydrophobic association polymer fracturing thickening agent and preparation method thereof

    CN119661772A

  • Disulfonate hydrophobic association polymer oil-displacing agent with benzene ring structure and preparation method of disulfonate hydrophobic association polymer oil-displacing agent

    CN119708342A

  • Method of fracturing subterranean formations using aqueous solutions comprising hydrophobically associating copolymers

    WO2020079123A1

Cited By

  • Self-suspending proppant based on nano-cellulose composite coating and preparation method of self-suspending proppant

    CN121471901A

  • A self-suspending proppant based on nanocellulose composite coating and a method of making

    CN121471901B